1964
DOI: 10.1901/jeab.1964.7-159
|View full text |Cite
|
Sign up to set email alerts
|

Exteroceptive Control of Response Under Delayed Reinforcement

Abstract: Three white rats, aftcr 50 continuous reinforcements, were exposed successively, under dim illumination, to reinforcement delays of 1, 3, 5, 7.5, 10, 15, and 20 sec, with prolonged training at the 20-sec level. Behavior was maintained at each level, and an increase in interval was accompanied by an increase in post-reinforcement pause. Subsequently, under both 20-and 30-sec delays, the animals were tested during half of each daily session to determine the effect of introducing darkness during each delay interv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
52
1
7

Year Published

1967
1967
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(70 citation statements)
references
References 3 publications
6
52
1
7
Order By: Relevance
“…The similarity of effects obtained in Experiment I with post-reinforcement pause and response rate under the variable-interval schedule supports and extends the findings of Azzi et al (1964), who reported that both variables were sensitive measures of delay of reinforcement effects when the initial schedule was continuous reinforcement.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…The similarity of effects obtained in Experiment I with post-reinforcement pause and response rate under the variable-interval schedule supports and extends the findings of Azzi et al (1964), who reported that both variables were sensitive measures of delay of reinforcement effects when the initial schedule was continuous reinforcement.…”
Section: Discussionsupporting
confidence: 86%
“…Three procedures for delaying reinforcer delivery were compared at each of the delay durations: a retracted lever procedure in which the lever was absent during the delay (Tombaugh, 1966); a fixed-delay procedure in which responses during the delay had no scheduled effect on delay duration (Dews, 1960;Silver and Pierce, 1969); and a DRO procedure in which each response during the delay restarted the delay (Skinner, 1938;Dews, 1960;Azzi, Fix, Keller, and Rocha e Silva, 1964).…”
Section: Methodsmentioning
confidence: 99%
“…In this case, reinforcement may strengthen a response sequence in which the first component is the lever-press response. Azzi, Fix, Keller, and Rocha e Silva (1964) have observed the development of such response sequences when the lever-press response was followed by a delay of reinforcement.…”
Section: Discussionmentioning
confidence: 99%
“…A importância desses livros para a introdução do behaviorismo no Brasil foi diversas vezes reconhecida (e.g., Todorov, 1990) (Bori, 1996;Keller, 1981;Matos, 1996Matos, , 1998. Trabalhando no Departamento de Fisiologia da faculdade por falta de laboratório no Departamento de Psicologia, sem equipamentos adequados e em precárias condições, Keller conseguiu ensinar com exercícios práticos, concluindo um experimento sobre o efeito do atraso de reforço na aprendizagem, posteriormente publicado no Journal of the Experimental Analysis of Behavior (JEAB) (Azzi, Fix, Keller & Rocha e Silva, 1964). O experimento foi realizado com uma gaiola de pássaros como câmara experimental, o rato ficava abrigado em outra gaiola, a tradicional barra de metal foi substituída por um arame, nada era elétrico nem automático, mas foi possível usar água como reforço (Kerbauy, 1983).…”
Section: Fred Keller E a Análise Do Comportamento No Brasilunclassified